Chronology and distribution of Pleistocene woolly rhinoceros: A review of the archival data from Poland - Pawłowska, Kamilla; Dedła, Kajetan; Płonka, Katarzyna (Geologos, 2024)
This work provides a review of the state of knowledge of woolly rhinoceroses in Poland. We compile research results from the 19th century to the present day and consider the collected data not only quantitatively, but above all qualitatively. Here we present a list of 215 sites from Poland where the remains of the woolly rhinoceros have been found. Studies of woolly rhinos from Poland usually employ small samples. Our compilation of data also reveals that there is currently no basis for drawing conclusions regarding the geographical distribution pattern of the species in Poland. Only a small number of works have focused on matching the places where remains occurred with the geological conditions of the area and their depositional history. Moreover, the results show that the resolution of the radiocarbon dates that are currently published is insufficient to allow conclusions about the chronology of woolly rhinoceroses in Poland to be drawn. No works to date have dealt with any aspect of palaeopopulation research. The woolly rhinoceros is not present in Palaeolithic art in Poland. A summary of our knowledge of this taxon is the starting point for our multi-aspect research into this topic.